UPAYA MENURUNKAN SCHOOL REFUSAL DENGAN TEKNIK KONSELING INDIVIDUAL STUDI KASUS SISWA SMA PGRI 10 GLENMORE - Raup Padillah; Dedi Agus Wahyudi; Heribertus Wicaksono (Program Studi Bimbingan dan Konseling, 2022)
The purpose of school is to promote intellectual, moral, and spiritual growth of students however, not all children feel that school is a fun time, which is caused by many factors such as the surrounding environment, peers, school, and themselves. their children's attitude if they refuse to go to school. Refusing school or known as Schooll Refusal. This study aims to find out the causes, how to handle, and find out the efforts to reduce School Refusal School Refusal, PGRI 10 Glenmore High School students, this study researchers used a qualitative approach with the type of Case Study Research (Case study). With the application of individual counseling services students can better and start diligently attending school and be able to behave well in school. so the application of individual counseling services is an effective way to deal with student school refusal cases, especially for students who have problems with school attendance, like to ask permission to go home first on the grounds of illness, and so on. Based on the research that has been done, it is concluded that the be a factor causing School Refusal in SMA PGRI 10 Glenmore students, namely the negative mindset of students towards the social environment at school both in terms of learning and in relationships. Efforts were made by providing individual counseling services to reduce student cases of School Refusal, with the implementation of individual counseling services seen changes in these students to attend school diligently and have positive behavior